If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6 + 5x = -4x + 57 Reorder the terms: 6 + 5x = 57 + -4x Solving 6 + 5x = 57 + -4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4x' to each side of the equation. 6 + 5x + 4x = 57 + -4x + 4x Combine like terms: 5x + 4x = 9x 6 + 9x = 57 + -4x + 4x Combine like terms: -4x + 4x = 0 6 + 9x = 57 + 0 6 + 9x = 57 Add '-6' to each side of the equation. 6 + -6 + 9x = 57 + -6 Combine like terms: 6 + -6 = 0 0 + 9x = 57 + -6 9x = 57 + -6 Combine like terms: 57 + -6 = 51 9x = 51 Divide each side by '9'. x = 5.666666667 Simplifying x = 5.666666667
| c=35+0.03 | | ln(2x+6)=7 | | 0.7W+164w=27.28 | | ln(2x+6)=6 | | 8x+2=114 | | s/5=-13 | | -3+13=12x-5-11x | | (2x-3)(2x+3)-4x(x+1)=2(x+3)+3 | | 2q-2=23 | | .35=.50 | | 2m-(x+2)=0 | | log4x=5/2 | | (X+2y)(x^3-2x^2y+4xy^2)= | | 3-1/2x=-5 | | 4x=-7y-37 | | 9x-3+2x+20=15+4x+2+7x | | 2x+17-7x-6=8-10x-19+5x | | (5x+3)2y=43 | | 5(3x+3)-5x=95 | | (3x-6)+(5x+9)= | | (7x+2)2= | | (7/9)+(5/6)=x | | 4a+7b=43 | | (4/9)-(1/2)=x | | 5s+20=150 | | x+.8x=25 | | 44=5x-4 | | X+2x=145 | | x+(3x-2)+(4x-4)= | | -40/21=x | | X+2y=145 | | 7(b+2)=4(b+2) |